Solution-focused Brief Counseling in Educational Setting: A Systematic Literature Review - Ida Ayu Made Diah Naraswari; Kadek Suranata; Ni Ketut Suarni; I Ketut Gading (Konselor, 2021)
The use of counseling models that are relevant to the problems and symptoms of psychological disorders is needed to support the implementation of effective counseling services, especially in educational setting. Solution-focused brief counseling (SFBC) is one of the counseling models that has recommended to be used in the implementation of counseling services. This study aims to reported the review of literature related to the used of SFBC in educational settings. Results of this study found that SFBC has been widely used in educational settings both in schools and universities. The most frequently used counseling techniques are the exception question technique and the miracle question technique. Psychological symptoms/disorders that can be intervened with SFBC include academic procrastination, aggressive behavior, anxiety and academic stress, as well as substance abuse and trauma. Results of this study have implications for the use of SFBC in educational setting.